PENGARUH MISI GEREJA KATOLIK PASKA KONSILI VATIKAN II DI KEUSKUPAN KETAPANG - Ranubaya, Fransesco Agnes; Meo, Yohanes Wilson B. Lena; Firmanto, Antonius Denny (Jurnal Euntes, 2023)
This study analyses the impact of the Second Vatican Council on the Catholic Church in Ketapang Diocese. The purpose of the study is to explain the mission movement, the history of changes in ecclesiastical structures, and the ecumenical principles introduced by the Second Vatican Council. The research method used is a literature study with a historical and narrative approach. The findings show that the Second Vatican Council has had a significant impact on the Catholic Church in Ketapang Diocese. The Church's mission movement is growing, reflected in the changing view of the relationship between the Church and the world, as well as between religions. Theological principles such as the teaching of love and respect for others have become central values in the Christian tradition. The Second Vatican Council also strengthened the role of the laity in the Church, underlining the responsibility of every member of the Church in mission. In addition, the Second Vatican Council opened the horizons of the Catholic Church of Ketapang Diocese in the context of mission to the whole world. The conclusion of this research confirms that the Second Vatican Council is not only a historical event of the Church, but also a source of inspiration that is relevant in facing today's challenges. The Catholic Church of Ketapang Diocese continues to strive to carry out the mission of Christ with a spirit inspired by the principles of the Second Vatican Council, maintaining theological integrity, and fidelity to Church teachings.